2020
DOI: 10.3390/ijms21072279
|View full text |Cite
|
Sign up to set email alerts
|

n–3 Polyunsaturated Fatty Acid Amides: New Avenues in the Prevention and Treatment of Breast Cancer

Abstract: Over the last decades a renewed interest in n−3 very long polyunsaturated fatty acids (PUFAs), derived mainly from fish oils in the human diet, has been observed because of their potential effects against cancer diseases, including breast carcinoma. These n−3 PUFAs mainly consist of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) that, alone or in combination with anticancer agents, induce cell cycle arrest, autophagy, apoptosis, and tumor growth inhibition. A large number of molecular targets of n−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 102 publications
(130 reference statements)
0
27
0
1
Order By: Relevance
“…Recent research suggests that a diet enriched with linoleic acid is related to a reduction in the incidence of cancer [ 32 , 33 ]. Linolenic and linoleic acids may act via different mechanisms to inhibit the development of some types of cancer, especially breast cancer [ 33 , 34 , 35 ]. The G1 sub-network contains: pristimerin [M + H] + m/z 465.3012; tingenone [M + H] + m/z 421.2745; 20-oxo-20,21-seco-tingen-21-oic acid [M + H] + m/z 453.263, and other unidentified derivatives in the database.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research suggests that a diet enriched with linoleic acid is related to a reduction in the incidence of cancer [ 32 , 33 ]. Linolenic and linoleic acids may act via different mechanisms to inhibit the development of some types of cancer, especially breast cancer [ 33 , 34 , 35 ]. The G1 sub-network contains: pristimerin [M + H] + m/z 465.3012; tingenone [M + H] + m/z 421.2745; 20-oxo-20,21-seco-tingen-21-oic acid [M + H] + m/z 453.263, and other unidentified derivatives in the database.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research suggests that a diet enriched with linoleic acid is related to a reduction in the incidence of cancer [32,33]. Linolenic and linoleic acids may act via different mechanisms to inhibit the development of some types of cancer, especially breast cancer [33][34][35] [36,37].…”
Section: Molecular Networkingmentioning
confidence: 99%
“…Notably, sleep disturbances themselves have been reported to be a risk factor for AD [60], and the identified reductions in CSF OEA would be consistent with such a physiological manifestation [61]. A recent study also suggested that the EPA-derived ethanolamide (EPEA) is a potential PPAR γ agonist [62], a transcription factor known for its neuroprotective and anti-inflammatory action [63]. Interestingly, non-fasting levels of EPEA showed positive association with MoCA in AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, omega-3 PUFAs may also act in combination with anticancer agents to induce cell cycle arrest improving the efficacy of some drugs, such as doxorubicin [ 109 ]. In addition, the biological effects of DHA and EPA can also be exerted by their derivative molecules including DHA-dopamine (DHADA) and EPA–dopamine (EPADA) conjugates as well as DHA-ethanolamine (DHEA) and EPA-ethanolamine (EPEA) [ 111 ]. In particular, DHADA and EPADA arrested cell cycle and reduced concomitantly S-phase in MCF-7, SK-BR-3 and MDA-MB-231 cells, indicating that these molecules induced cell cycle arrest in breast cancer cells, independently of ER/PR/HER2 status [ 70 ].…”
Section: Anticancer Mechanismsmentioning
confidence: 99%